Technology vs information to promote conservation: Evidence from water audits - Erik Ansink; Carmine Ornaghi; Mirco Tonin (Tinbergen Institute, 2021)
We study the impact of audits on water conservation, distinguishing between the information and technological components. We observe water consumption for up to 18 months for 10,000 households in the South East of England who received the visit of a so-called Green Doctor. We find that water-saving devices decrease water consumption by 2-4%, with an effect that is persistent over 18 months. Devices reducing water pressure are particularly effective, while shower timers are ineffective. The information component of the water audit has a large initial impact, but this gradually fades to a drop in consumption of 2% after 12 months. Technology appears to be more cost-effective than information provision and this can help in the design of policy interventions.
Keywords: Q25; H42; D12; L95; 330; Water audits; Green Doctors; conservation; information; technology